Intellectual property rights and North-South trade: Exports vs. foreign direct investment - Dong, Quan; Bárcena-Ruiz, Juan Carlos; Begoña Garzón, María (Estudios de Economía, 2022)
This paper examines whether a Northern firm prefers to export or to engage in FDI to serve the South. If the firm engages in FDI, its technology is imitated, and a Southern firm enters the market that may sell in both markets. The Northern firm may invest to prevent product piracy in the North. The two markets may have different sizes. We find that when the cost of preventing product piracy in theNorth is great enough: (i) If the Southern market is large enough the Northern firm engages in FDI, allowing piracy in its home market, and the South obtains the greater welfare; (ii) If the Southern market is small enough the Northern firm exports and the government of the South imposes a strong Intellectual Property Rights protection, attracting the Northern firm and improving the welfare of both countries.